A Comparison of Parametric and Sample-Based Message Representation in Cooperative Localization. (12th September 2012) - Lien, Jaime; Ferner, Ulric J.; Srichavengsup, Warakorn; Wymeersch, Henk; Win, Moe Z.
Abstract : Location awareness is a key enabling feature and fundamental challenge in present and future wireless networks. Most existing localization methods rely on existing infrastructure and thus lack the flexibility and robustness necessary for large ad hoc networks. In this paper, we build upon SPAWN (sum-product algorithm over a wireless network), which determines node locations through iterative message passing, but does so at a high computational cost. We compare different message representations for SPAWN in terms of performance and complexity and investigate several types of cooperation based on censoring. Our results, based on experimental data with ultra-wideband (UWB) nodes, indicate that parametric message representation combined with simple censoring can give excellent performance at relatively low complexity.